2013
DOI: 10.3171/2013.9.peds13187
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral foreign body granuloma caused by a resorbable plate with passive intraosseous translocation after cranioplasty

Abstract: Numerous reports have demonstrated the usefulness of bioresorbable materials, but few have described severe complications caused by delayed degradation. The authors present the case of an intracranial foreign body granuloma caused by plates made of unsintered hydroxyapatite (uHA) particles and poly-l-lactide (PLLA; Super Fixsorb MX, Takiron) after cranioplasty. This 1-month-old boy presented to the authors' department with Pfeiffer syndrome. He had multiple-suture synostosis causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…They do not require any secondary operation for removal due to their characteristics. Thus, bioabsorbable plates and screws are commonly used to reduce maxillofacial bones, particularly in pediatric patients [ 7 ]. Polyglycolic acid (PGA) and polylactic acid (PLA) are the polymers used most widely to manufacture bioabsorbable plates and screws [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They do not require any secondary operation for removal due to their characteristics. Thus, bioabsorbable plates and screws are commonly used to reduce maxillofacial bones, particularly in pediatric patients [ 7 ]. Polyglycolic acid (PGA) and polylactic acid (PLA) are the polymers used most widely to manufacture bioabsorbable plates and screws [ 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This supporting method was effective in eight of 10 patients. However, infection of anchor pins occurred in one patient, and a foreign body granuloma in temporal lobe caused by passive intraosseous translocation of a resorbable plate occurred in one patient 16) .…”
Section: Clinical Results Of Mcdo In Our Institutementioning
confidence: 98%
“…Thus, these authors indicated that skin incision areas were associated with the delayed absorption as compared with healthy tissues with adequate blood supplies. Katsuragi et al [ 6 ] also reported that intracerebral FBGs occurred on the temple, a thin-skinned area, as well as incision sites after using PLLA. Thus, the infraorbital rim and frontozygomatic buttress are often close to or in contact with the sites where the plate is fixed and where the skin incision is performed.…”
Section: Discussionmentioning
confidence: 99%